Probing the interaction of Hepatitis C virus glycoproteins with putative receptors and neutralising antibodies - Mirza, Deeman (2012)
Hepatitis C virus (HCV) is a hepatotropic blood-borne virus which causes chronic hepatitis in the majority of cases and represents a global health burden. In order for HCV to enter cells, proteins on the surface of the virus must interact and bind to receptors on target cells. HCV surface molecules involved with receptor binding, and cellular entry, as well as immune escape, are the glycoproteins E1 and E2. The cellular receptors SRBI, CD81, CLDNs and most recently occludin have been shown to facilitate HCV entry into hepatocytes. Several conservative regions on E1E2 have, through substitution mutagenesis, proven to be important for receptor binding and antibody neutralisation. We aimed to characterise one discontinuous region, amino acid residues 611, 613-619 and 621, and its role in the interaction with CD81 by single alanine substitution mutagenesis. Mutant plasmids were transfected into HEK 293FT cells and assessed for protein expression and binding by conformation-sensitive, CD81-inhibiting antibodies. Also, to investigate whether a conformational change of the E1E2 occurs upon SRB1 binding, rendering the CD81 binding domains accessible, two assays have been compared. A plate based experiment, exclusive of SRBI and a cell based assay, including SRBI was designed to examine the antigenic exposure of the CD81 binding regions to targeting monoclonal antibodies. Additionally, Huh-7 cells expressing different levels of SRBI were used to investigate whether some HCVpp isolates rely on high SRB1 levels for infectivity and sensitivity to neutralising antibodies. These studies were performed to help elucidate the regions and residues important in HCV E1E2: receptor interaction and their interplay with each other and with neutralising antibodies.